Beberapa Permasalahan dalam Menjadi Penerjemah Sastra yang Baik - Sunardi, FX Dono (Jurnal Penerjemahan, 2023)
Literary translation transcends the boundaries of a mere translation discipline and assumes the profound responsibility of preserving narratives that serve as foundational elements of human civilization. Combining the skills of translation with the artistry of creative writing, literary translation surpasses the conventional expectations of a translator. A literary translator bears the weighty task of not only conveying the message and meaning of a translated work but also encapsulating its aesthetic essence. This scholarly article delves into anexploration of five primary challenges encountered in the realm of literary translation, alongside an examination of fidelity as the fundamental principle governing the translation of literary works. It is crucial toacknowledge that the notion of an ideal and flawless literary translation, and consequently an ideal literary translator, remains elusive. Rather, the pinnacle of literary translation lies in the production of a translationthat progressively approximates the intended meaning and form of the original work. Keywords:Fidelity, message/meaning and form, skill and arts